2004
DOI: 10.1074/jbc.m405300200
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of a Salt Bridge Dramatically Accelerates Subunit Exchange in Duck δ2 Crystallin

Abstract: Intragenic complementation is a unique property of oligomeric enzymes with which to study subunit-subunit interactions. Complementation occurs when different subunits, each possessing distinct mutations that render the individual homomutant proteins inactive, interact to form a heteromutant protein with partial recovery of activity. In this paper, complementation events between human argininosuccinate lyase (ASL) and its homolog, duck ␦2 crystallin, were characterized. Different active site mutants in ␦2 cryst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…It has been reported that a predicted salt-bridge interaction between Arg 173 and Glu 318 in a GPCR was not interchangeable as judged in studies on the receptor containing the reciprocal mutation (43). In addition, although the interaction between Arg 302 and Glu 330 was identified in the crystal structure of crystallin, the R302E/E330R reciprocal mutation showed 31% of WT activity, which is equivalent to the activity of E330R mutant (44). These results suggest that a saltbridge interaction is not always interchangeable and may account for the suppression of constitutive activity by the introduction of N205D/ Y266K but not N025K/Y266D into the P258L/S259L constitutively active mutant.…”
Section: Discussionmentioning
confidence: 98%
“…It has been reported that a predicted salt-bridge interaction between Arg 173 and Glu 318 in a GPCR was not interchangeable as judged in studies on the receptor containing the reciprocal mutation (43). In addition, although the interaction between Arg 302 and Glu 330 was identified in the crystal structure of crystallin, the R302E/E330R reciprocal mutation showed 31% of WT activity, which is equivalent to the activity of E330R mutant (44). These results suggest that a saltbridge interaction is not always interchangeable and may account for the suppression of constitutive activity by the introduction of N205D/ Y266K but not N025K/Y266D into the P258L/S259L constitutively active mutant.…”
Section: Discussionmentioning
confidence: 98%
“…9, A and B). The second occurs when a stable mutant subunit and an unstable mutant subunit form a hybrid protein with enough overall stability for catalysis to occur (24).…”
Section: Discussionmentioning
confidence: 99%
“…Disruption of salt bridges thereby facilitates subunit movement [65] and thereby modulates stability of higher order oligomeric protein structures. Salt at high concentration is known to inhibit self assembly of individual subunits in protein oligomers [43,66].…”
Section: Salt Disrupts Inter-subunit Salt Bridges In Hrad52 Oligomersmentioning
confidence: 99%